THE DEVELOPMENT OF CHARACTER EDUCATION MODEL TROUGH AN INTEGRATED CURRICULUM AT ELEMENTARY EDUCATION LEVEL IN MEDAN CITY - Amini Amini Amini; Syamsu Yurnita Yurnita; Hasnidar Hasnidar Hasnidar (State Islamic University of North Sumatra Indonesia, 2017)
Character education is an effort to help the development of the soul of children/learners both inward and inward to a better human. Therefore character education is a continuous and never-ending process, in order to produce a future human figure rooted in the cultural values of the Indonesian nation. Thus character education has a higher meaning than moral education because character education is not only about right-wrong problems, but how to instill habits of good things in life, so that children/learners will have awareness, and high understanding, as well as concern and commitment to apply the virtues in everyday life. Character education in today's context is very relevant to children/learners to overcome the moral crisis that is happening in our country. Whether or not this real moral crisis exists that involves our generation is our children as future leaders. The crisis is among others promiscuity, a crime against friends, teenage theft, cheating habits, drug abuse and drugs, pornography, and so forth. This should be addressed early on by characterizing character education through an integrated curriculum to children/learners. This is done by researchers as a continuation of research activities in 2015 with the object of basic education research in Muhammadiyah Elementary School 29 of Sunggal. The year 2016 was continued again in Muhammadiyah Junior High School 47 of Sunggal as part of basic education. Because the so-called elementary education is elementary (primary school) and junior (junior high school) equal. This research was conducted to see the development of character education model conducted in SMP Muhammadiyah 47 Sunggal through an integrated curriculum. Because so far there is a stigma that the character education is only the responsibility of teachers REM and PCE in school, so that dichotomous character education (only inculcated by both teachers while other teachers do not do). It turns out through an integrated curriculum that character education is willing or not to be inculcated by all teachers and school residents. So the model of character education today is through 2 approaches, character education is positioned as the subject itself and character education is positioned as the mission of every subject (integrated into each subject). This research is conducted as an effort to assist the government in anticipating and overcoming the moral crisis that occurs in order to prepare a generation that character in the futureKeywords: Character Education Model, Integrated Curriculum, Elementary Education Level.